2019
DOI: 10.3390/fi11050103
|View full text |Cite
|
Sign up to set email alerts
|

Computational Social Science of Disasters: Opportunities and Challenges

Abstract: Disaster events and their economic impacts are trending, and climate projection studies suggest that the risks of disaster will continue to increase in the near future. Despite the broad and increasing social effects of these events, the empirical basis of disaster research is often weak, partially due to the natural paucity of observed data. At the same time, some of the early research regarding social responses to disasters have become outdated as social, cultural, and political norms have changed. The digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 213 publications
(222 reference statements)
0
9
0
Order By: Relevance
“…The CSSD provides new theoretical grounds to investigate the complexities and the interacting processes involving traditional social sciences of disasters, computational social science, and crisis informatics. However, there is still a challenge in the collection and handling of human subject data [19]. Hawe et al revealed that Agent-based simulations (ABS) have become the de-facto technique for determining the best way to respond to a large-scale emergency.…”
Section: Existing Evacuation Simulation Modelmentioning
confidence: 99%
“…The CSSD provides new theoretical grounds to investigate the complexities and the interacting processes involving traditional social sciences of disasters, computational social science, and crisis informatics. However, there is still a challenge in the collection and handling of human subject data [19]. Hawe et al revealed that Agent-based simulations (ABS) have become the de-facto technique for determining the best way to respond to a large-scale emergency.…”
Section: Existing Evacuation Simulation Modelmentioning
confidence: 99%
“…Be it pandemic or disasters, it is predicted to continue and having a great impact on the socio-economic welfare of the entire world [1]. Authorities of emergency management service use several Emergency Response Computational Tool and Models (ERT) to route resources; however, advantages and limitations of such tools is not always clear [2].…”
Section: Introductionmentioning
confidence: 99%
“…Within the internet science community, there had been many efforts to improve collective decision-making by means of specific technologies [1][2][3][4]. For example, understanding how people reason (and, eventually, commit mistakes) at individual level or in group is crucial to improve the design of online crowdsourcing systems and software [5,6]. In this paper, we investigate a paradigmatic reasoning error, the conjunction fallacy.…”
Section: Introductionmentioning
confidence: 99%